Peran Posyandu Lansia Dalam Meningkatkan Kesehatan Dan Kualitas Hidup Pada Usia Lanjut - Suryati Suryati; Hartika Utami Fitri; Tika Rahmawati (Journal of Innovative and Creativity, 2025)
This study aims to analyze the role of the Elderly Posyandu (Integrated Health Post for the Elderly) in improving the health and quality of life of the elderly in Talang Kemang Village and identify obstacles that hinder its implementation. The approach used was a qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that the Elderly Posyandu plays a significant role in providing health services such as blood pressure checks, weighing, nutrition counseling, and social activities that support the physical and mental well-being of the elderly. However, the implementation of Posyandu activities still faces various obstacles, such as limited health workers, minimal facilities and infrastructure, and low participation of the elderly due to physical limitations, transportation, and lack of awareness. Support from families and communities also still needs to be improved. In conclusion, despite these various obstacles, the Elderly Posyandu in Talang Kemang Village is able to make a real positive contribution in efforts to maintain and improve the health and quality of life of the elderly through a promotive, preventive, and participatory approach.